Composite diaphragm as well as preparation method and application thereof
By applying a modified coating on the base film of the flow battery separator to form a composite separator, the problem of active substance shuttle in the existing separator is solved, and the coulomb efficiency and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411566205.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing flow battery separators have poor ion selective permeability, which leads to the easy shuttle of active substances in the electrolyte and reduces the balun efficiency and cycle life of the battery.
A composite diaphragm is used, which consists of a base film and a modified coating. The modified coating is composed of carbon material, mesoporous material and metal oxide. By applying a modified coating on the surface of the base film, three layers or The double-layer structure enhances adhesion and reduces the average pore size of the surface layer of the diaphragm, blocking the shuttle of active substances.
It improves the Coulomb efficiency and cycle stability of the flow battery, extends the service life of the battery, and realizes screening and conduction of different ions.
Smart Images

Figure CN119481127A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of liquid flow batteries, and in particular to a composite diaphragm and a preparation method and application thereof. Background Art
[0002] Energy storage technology is a key technology to achieve the effective utilization of intermittent renewable energy and promote the development of smart and microgrids. In recent years, aqueous flow batteries have attracted widespread attention in the field of large-scale / long-term energy storage due to their intrinsic safety and energy-power decoupling. Flow batteries use the changes in the valence state of active substances in the positive and negative electrolytes during the charging and discharging process to achieve energy storage and release. The flow battery systems that have been successfully developed include all-vanadium flow batteries, iron-chromium flow batteries, zinc-bromine flow batteries, sulfur-iodine flow batteries, sulfur-iron flow batteries, sulfur-bromine flow batteries, tin-iodine flow batteries, organic flow batteries, etc.
[0003] The diaphragm is an important component of the flow battery. In the battery, it not only separates the positive and negative electrodes to prevent the battery from short-circuiting, but also provides a channel for the transfer of charge carriers in the positive and negative electrolytes to form a battery circuit. An ideal flow battery diaphragm should have the characteristics of high carrier conductivity, high ion selective permeability, excellent chemical and electrochemical stability, and low cost. At present, flow batteries are still in the early stages of commercialization, and perfluorosulfonic acid cation exchange membranes dominate the flow battery membrane market because of their excellent chemical stability and high carrier conductivity.
[0004] However, due to the poor ion permeability of ion exchange membranes, especially perfluorosulfonic acid cation exchange membranes, the active substances in the positive and negative electrolytes can easily pass through the ion exchange membranes into the counter electrode, resulting in active substance shuttling. This phenomenon not only reduces the coulombic efficiency of the flow battery, but is also usually accompanied by irreversible side reactions, generating insulating or electrochemically inactive byproducts, which increases the internal resistance of the battery and ultimately reduces the battery capacity and cycle life. In sulfur-based flow batteries, iodine-based flow batteries, and bromine-based flow batteries, the sharp drop in capacity caused by severe active substance shuttling has seriously hindered the development and commercialization of the system. Summary of the invention
[0005] The present application provides a composite diaphragm and a preparation method and application thereof. During the charge and discharge process of a liquid flow battery, the composite diaphragm can inhibit the shuttling of active substances in the electrolyte, improve the ion selective permeability of the diaphragm, and help improve the coulombic efficiency of the liquid flow battery, so that the liquid flow battery can be cycled stably for a long time and the service life of the battery is extended.
[0006] In order to solve the above technical problems, one of the purposes of the present application is to provide a composite diaphragm, the composite diaphragm comprising a base film and a modified coating located on one side or two opposite sides of the base film, the base film comprising an intermediate layer and a transition layer formed in one piece, the base film is made of a polymer resin, the transition layer is located between the intermediate layer and the modified coating, and the transition layer is formed by the components of the modified coating penetrating into the base film;
[0007] The components of the modified coating include fillers and binders, the mass ratio of the fillers to the binders is 8:(0.5-5), and the fillers are at least one of carbon materials, mesoporous materials, and metal oxides.
[0008] The composite diaphragm of the present application forms a three-layer or double-layer structure by coating a modified coating slurry on the surface of a base membrane. The binder and other components of the modified coating penetrate into the base membrane to form a transition layer to strengthen the bonding. The modified coating reconstructs the surface structure of the composite diaphragm, and the average pore size of the surface layer of the diaphragm is reduced. When used in liquid flow batteries for charging and discharging, it can block the shuttling of active substances in the electrolyte, hinder the cross-mixing of positive and negative active substances, and avoid the shuttling and degradation of active substances that lead to capacity decay of the liquid flow battery; at the same time, the composite diaphragm can also realize the screening conduction of different ions, effectively improve the ion selective permeability, significantly improve the coulombic efficiency of the liquid flow battery, and make the liquid flow battery have excellent cycle stability.
[0009] As a preferred embodiment, the carbon material includes but is not limited to at least one of Ketjen black (KB), acetylene black (AB), Super P (SP), activated carbon (AC), carbon nanotube (CNT) and graphene.
[0010] As a preferred embodiment, the mesoporous material is at least one of titanium dioxide, silicon dioxide, aluminosilicate and aluminum oxide.
[0011] As a preferred embodiment, the specific surface area of the filler is 10-3000m 2 / g.
[0012] As a preferred embodiment, the particle size of the mesoporous material is 30-100 nm, and the specific surface area is 20-300 m 2 / g.
[0013] As a preferred embodiment, the specific surface area of the carbon material is 500-1500m 2 / g.
[0014] As a preferred embodiment, the iodine adsorption value of the carbon material is above 500 mg / g.
[0015] The inventors have discovered that the higher specific surface area and iodine adsorption value of the carbon material in the composite diaphragm can effectively adsorb charged active substances in the electrolyte, forming a charged protective barrier on the surface of the diaphragm, effectively hindering the shuttling of active substances in the flow battery and improving the coulombic efficiency. However, the higher the specific surface area, the larger the size of the carbon material will be, thereby affecting the pore size on the surface of the composite diaphragm. Therefore, controlling the specific surface area and iodine adsorption value of the carbon material of the present application within the above range can maximize the ability of the diaphragm to inhibit the shuttling of active substances, especially during the charging and discharging process of the sulfur-iodine flow battery, to ensure the battery cycle stability.
[0016] As a preferred embodiment, the particle size of the metal oxide is 30-100 nm.
[0017] As a preferred embodiment, the filler is a carbon material, preferably at least one of Ketjen black and activated carbon.
[0018] Since carbon materials have high conductivity, the modified coating in the composite diaphragm of the present application has higher conductivity when using carbon materials such as Ketjen black or activated carbon, which can improve the conductivity of the electrochemical reaction interface and enhance the energy efficiency of the flow battery.
[0019] As a preferred embodiment, the binder includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP) and at least one of the modified materials of the aforementioned substances. The binder of the present application has high viscosity and chemical stability, that is, it can strengthen the fixation of the modified coating and the base membrane, while also ensuring the stability of the composite diaphragm.
[0020] As a preferred solution, the binder is polyvinylidene fluoride.
[0021] As a preferred embodiment, the polymer resin includes but is not limited to at least one of perfluorosulfonic acid resin, polysulfone resin, polyimide resin, polyvinylidene fluoride resin, polyaryletherketone resin, polyethersulfone resin, polybenzimidazole resin, polyacrylamide resin, sulfonated polysulfone resin, sulfonated polyimide resin, sulfonated polyvinylidene fluoride resin, sulfonated polyaryletherketone resin, sulfonated polyethersulfone resin, sulfonated polybenzimidazole resin and sulfonated polyacrylamide resin.
[0022] As a preferred embodiment, the polymer resin is a perfluorosulfonic acid cation exchange resin.
[0023] As a preferred embodiment, the slurry of the modified coating includes fillers and an organic solvent containing a binder. The organic solvent can act on the surface of the base membrane to cause it to swell, making it easier for the binder to penetrate into the base membrane to form a transition layer to strengthen bonding. The modified coating formed after drying reconstructs the surface structure of the composite membrane, and the average pore size of the membrane surface is reduced, which can effectively improve the ion selective permeability of the membrane.
[0024] As a preferred solution, the mass fraction of the binder in the organic solvent containing the binder is 0.01wt%-5wt%.
[0025] As a preferred embodiment, the mass ratio of the filler to the binder is 8:(1-3).
[0026] As a preferred embodiment, the organic solvent includes but is not limited to at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, n-propanol, isopropanol, ethanol, isobutanol, tetrahydrofuran, ethylene glycol, methanol, dimethyl sulfoxide, and acetonitrile. The organic solvent can swell the base film to facilitate the penetration of the adhesive, and can be completely evaporated during the drying process of the modified coating without any organic solvent residue.
[0027] As a preferred embodiment, the slurry of the modified coating further includes additives, and the additives include but are not limited to at least one of a surfactant, a defoamer, and a catalyst.
[0028] As a preferred solution, the thickness of the modified coating is 5-15 μm.
[0029] In order to solve the above technical problems, the second object of the present application provides a method for preparing a composite diaphragm, comprising the following steps:
[0030] (1) dissolving a binder in an organic solvent, adding a filler, and dispersing the mixture uniformly to obtain a slurry;
[0031] (2) The slurry is evenly coated on one side or two opposite sides of the base film and dried to obtain a composite diaphragm.
[0032] As a preferred embodiment, in step (1), the binder has a mass fraction of 0.05wt%-5wt% when dissolved in an organic solvent.
[0033] As a preferred embodiment, in step (1), the organic solvent is at least one of N-methylpyrrolidone and isopropanol.
[0034] As a preferred embodiment, in step (1), the dispersion method is ultrasonic dispersion, the dispersion time is 10-60 min, and the ultrasonic frequency is 10-30 kHz.
[0035] As a preferred embodiment, in step (2), the base membrane is a potassium-type perfluorosulfonic acid cation exchange resin membrane obtained by activation treatment of a perfluorosulfonic acid cation exchange resin membrane.
[0036] As a preferred embodiment, in step (2), the activation treatment method includes the following steps: placing the perfluorosulfonic acid cation exchange resin membrane in a H2O2 aqueous solution, heat-insulating it, taking it out and placing it in an acidic aqueous solution for heat-insulating it, then placing it in an alkaline aqueous solution for heat-insulating it, and washing it to obtain a basement membrane.
[0037] As a preferred embodiment, in the activation treatment method, the mass fraction of H2O2 in the H2O2 aqueous solution is 3wt%-10wt%.
[0038] As a preferred embodiment, in the activation treatment method, the perfluorosulfonic acid cation exchange resin membrane is kept in the H2O2 aqueous solution at a temperature of 60-100°C for a time of 0.5-2h.
[0039] As a preferred embodiment, in the activation treatment method, the mass fraction of the acid in the acidic aqueous solution is 3wt%-10wt%.
[0040] As a preferred embodiment, in the activation treatment method, the perfluorosulfonic acid cation exchange resin membrane is kept in the acidic aqueous solution at a temperature of 60-100° C. for a time of 0.5-2 h.
[0041] As a preferred embodiment, the acid in the acidic aqueous solution includes but is not limited to at least one of H2SO4, HCl, and HNO3.
[0042] As a preferred embodiment, in the activation treatment method, the concentration of the alkali in the alkaline aqueous solution is 0.5-2 mol / L.
[0043] As a preferred embodiment, in the activation treatment method, the perfluorosulfonic acid cation exchange resin membrane is kept in the alkaline aqueous solution at a temperature of 50-70° C. for a time of 2-4 hours.
[0044] As a preferred embodiment, the alkali in the alkaline aqueous solution includes but is not limited to at least one of KOH, NaOH, and Ca(OH)2.
[0045] As a preferred embodiment, in step (2), the coating amount is 5-1000 μL / cm 2 .
[0046] As a preferred embodiment, in step (2), the coating amount is 10-100 μL / cm 2 .
[0047] As a preferred embodiment, in step (2), the drying temperature is 60-120° C. and the drying time is 5-15 h.
[0048] In order to solve the above technical problems, the third purpose of the present application provides an application of a composite diaphragm in the preparation of a liquid flow battery, wherein the liquid flow battery is a sulfur-based liquid flow battery, an iodine-based liquid flow battery or a bromine-based liquid flow battery.
[0049] As a preferred embodiment, the sulfur-based flow battery includes but is not limited to one of a sulfur-iodine flow battery, a sulfur-iron flow battery, a sulfur-manganese flow battery, a zinc-sulfur flow battery, a sulfur-bromine flow battery, and a sulfur-organic flow battery.
[0050] As a preferred embodiment, the iodine-based flow battery includes but is not limited to one of a sulfur-iodine flow battery, a tin-iodine flow battery, a zinc-iodine flow battery, an organic-iodine flow battery, and a heteropolyacid-iodine flow battery.
[0051] As a preferred embodiment, the bromine-based flow battery includes but is not limited to one of a sulfur-bromine flow battery, a tin-bromine flow battery, a zinc-bromine flow battery, an organic-bromine flow battery, and a heteropolyacid-bromine flow battery.
[0052] As a preferred embodiment, the liquid flow battery comprises a positive electrode electrolyte, a negative electrode electrolyte and a diaphragm, the positive and negative electrode electrolytes contain active substances, and the diaphragm is one of the above-mentioned composite diaphragms that effectively inhibits the shuttling of active substances.
[0053] As a preferred embodiment, the positive electrode electrolyte of the sulfur-iodine liquid flow battery is a KI aqueous solution, the negative electrode electrolyte is a KOH aqueous solution, and the active substance of the negative electrode electrolyte is K2S2.
[0054] As a preferred embodiment, the positive electrode electrolyte of the sulfur-iodine flow battery is a 0.5-6 mol / L KI aqueous solution, the negative electrode electrolyte is an aqueous solution containing 0.01-2 mol / L KOH, and the concentration of the active substance K2S2 in the negative electrode electrolyte is 0.5-5 mol / L.
[0055] As a preferred embodiment, the positive electrode electrolyte of the sulfide iron flow battery is an aqueous solution containing ferrocyanide, the negative electrode electrolyte is an aqueous solution of KOH, and the active substance of the negative electrode electrolyte is K2S4. As a preferred embodiment, the positive electrode electrolyte of the sulfide iron flow battery is an aqueous solution containing 0.5-1.6 mol / L ferrocyanide, the negative electrode electrolyte is an aqueous solution containing 0.01-2 mol / L KOH, and the concentration of K2S4, the active substance of the negative electrode electrolyte, is 0.5-2 mol / L.
[0056] As a preferred embodiment, the ferrocyanide includes but is not limited to at least one of lithium ferrocyanide, sodium ferrocyanide, potassium ferrocyanide and ammonium ferrocyanide.
[0057] As a preferred embodiment, the ferrocyanide is 0.3-0.8 mol / L K4Fe(CN)6 and 0.3-0.8 mol / LNa4Fe(CN)6.
[0058] As a preferred embodiment, the positive electrode electrolyte of the tin-iodine liquid flow battery is a KI aqueous solution, the negative electrode electrolyte is a KOH aqueous solution, and the active substance of the negative electrode electrolyte is K2Sn(OH)6.
[0059] As a preferred embodiment, the positive electrode electrolyte of the tin-iodine liquid flow battery is an aqueous solution containing 0.5-6 mol / L KI, the negative electrode electrolyte is an aqueous solution containing 0.5-2 mol / L KOH, and the concentration of the active substance K2Sn(OH)6 in the negative electrode electrolyte is 0.5-2.25 mol / L.
[0060] Compared with the prior art, this application has the following beneficial effects:
[0061] 1. The composite diaphragm of the present application is coated with a modified slurry containing fillers and binders on the surface of the base membrane, so that the surface structure of the composite diaphragm is reconstructed and the average pore size of the surface layer is reduced. When used in liquid flow batteries for charging and discharging, it can block the shuttling of active substances in the electrolyte, hinder the cross-mixing of positive and negative active substances, and improve the ion selective permeability of the diaphragm, so that the coulombic efficiency and discharge specific capacity of the liquid flow battery are significantly improved, and it has excellent cycle stability.
[0062] 2. The carbon material used as the filler in the modified coating of the diaphragm of the present application has high conductivity, which can improve the conductivity of the electrochemical reaction interface to ensure that electrons are transmitted quickly and effectively during the charging and discharging process, improve energy efficiency, and ensure efficient and stable operation of the battery.
[0063] 3. The higher specific surface area of the carbon material in the composite diaphragm can adsorb charged active substances in the electrolyte, forming a charged protective barrier on the surface of the diaphragm, effectively hindering the shuttling of active substances in the flow battery and improving the coulombic efficiency. However, the higher the specific surface area, the larger the size of the carbon material will be, thereby affecting the pore size on the surface of the composite diaphragm. The present application controls the specific surface area and iodine adsorption value of the carbon material to maximize the ability of the diaphragm to inhibit the shuttling of active substances and ensure the cycle stability of the battery.
[0064] 4. The composition and thickness of the surface modification layer of the composite membrane prepared in this application are controllable. By adjusting the parameters, the battery performance can be controlled. The preparation method of the composite membrane is diverse and highly controllable, and has a process basis for large-scale mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 : is a schematic diagram of the structure of a composite diaphragm in an embodiment of the present application;
[0066] Figure 2 : The specific discharge capacity of the sulfur-iodine flow battery cycle process assembled by preparing the diaphragm in Example 1 of the present application;
[0067] Figure 3 : The coulombic efficiency of the diaphragm assembled sulfur-iodine flow battery cycle process prepared in Example 1 of the present application;
[0068] Figure 4 : A scanning electron microscope image of a cross section of a diaphragm prepared in Example 2 of the present application;
[0069] Figure 5 : The specific discharge capacity of the sulfur-iodine flow battery cycle process assembled by preparing the diaphragm in Example 2 of the present application;
[0070] Figure 6 : The coulombic efficiency of the diaphragm assembled sulfur-iodine flow battery cycle process prepared in Example 2 of the present application;
[0071] Figure 7 : The discharge specific capacity of the sulfur-iodine flow battery cycle process assembled by preparing the diaphragm in Comparative Example 1 of the present application;
[0072] Figure 8 : The coulombic efficiency of the diaphragm assembled sulfur-iodine flow battery cycle process prepared in Comparative Example 1 of the present application;
[0073] Fig. 9 : A scanning electron microscope image of a cross section of a diaphragm prepared in Example 3 of the present application;
[0074] Fig.10 : The discharge specific capacity of the sulfide-iron liquid flow battery cycle process assembled by preparing the diaphragm in Example 3 of the present application;
[0075] Fig.11 : The coulombic efficiency of the sulfide-iron flow battery cycle process assembled by preparing the diaphragm in Example 3 of the present application;
[0076] Fig.12 : The discharge specific capacity of the sulfide iron liquid flow battery cycle process assembled by preparing the diaphragm in Example 4 of the present application;
[0077] Fig.13 : The coulombic efficiency of the sulfide-iron flow battery cycle process assembled by preparing the diaphragm in Example 4 of the present application;
[0078] Fig.14 : The discharge specific capacity of the sulfide-iron liquid flow battery cycle process assembled by preparing the diaphragm in Example 5 of the present application;
[0079] Fig.15 : The coulombic efficiency of the sulfide-iron liquid flow battery cycle process prepared by diaphragm assembly in Example 5 of the present application;
[0080] Fig.16 : The discharge specific capacity of the sulfide-iron liquid flow battery cycle process assembled by preparing the diaphragm in Comparative Example 1 of the present application;
[0081] Fig.17: The coulombic efficiency of the sulfide-iron liquid flow battery cycle process assembled by preparing the diaphragm in comparative example 1 of the present application;
[0082] Fig.18 : The specific capacity of the first cycle of the tin-iodine liquid flow battery assembled with the diaphragm prepared in Comparative Example 2 of the present application;
[0083] Fig.19 : The specific capacity of the first cycle of the tin-iodine flow battery assembled with the diaphragm prepared in Example 6 of the present application;
[0084] Fig. 20 : The specific capacity of the first cycle of the tin-iodine flow battery assembled with the diaphragm prepared in Comparative Example 1 of the present application;
[0085] Fig.21 : The specific capacity of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 2 of the present application;
[0086] Fig. 22 : The coulombic efficiency of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 2 of the present application;
[0087] Fig.23 : The discharge specific capacity of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 4 of the present application;
[0088] Fig.24 : The coulombic efficiency of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 4 of the present application;
[0089] Fig.25 : The discharge specific capacity of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 5 of the present application;
[0090] Fig.26 : The coulombic efficiency of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Example 5 of the present application;
[0091] Fig. 27 : The discharge specific capacity of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Comparative Example 1 of the present application;
[0092] Fig.28 : The coulombic efficiency of the riboflavin sodium phosphate-iron battery cycle process assembled by preparing the diaphragm in Comparative Example 1 of the present application;
[0093] Fig.29 : A digital photo of a diaphragm-assembled H-type electrolytic cell prepared in Example 2 of the present application;
[0094] Fig.30 : A digital photo of a diaphragm-assembled H-type electrolytic cell prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0095] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0096] Unless otherwise specified, the test methods used in the examples and comparative examples of the present application are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0097] Table 1 - Sources of raw materials in the examples or comparative examples of this application
[0098]
[0099] Example 1
[0100] A method for preparing a composite diaphragm comprises the following steps:
[0101] (1) placing the cut perfluorosulfonic acid cation exchange resin membrane in a 5wt% H2O2 aqueous solution, keeping it at 80°C for 1h, taking out the membrane and placing it in a 5wt% H2SO4 aqueous solution, keeping it at 80°C for 1h; then placing the membrane in a 1mol / L KOH aqueous solution, keeping it at 60°C for 3h, and finally soaking the membrane in deionized water for standby use, to obtain a potassium-type perfluorosulfonic acid cation exchange membrane;
[0102] (2) Polyvinylidene fluoride (PVDF) was dissolved in N-methylpyrrolidone (NMP) to obtain a transparent polymer solution with a mass fraction of 1 wt%. Ketjen black (KB) was weighed and added to the transparent polymer solution. The specific surface area of KB was 1270 m 2 / g, iodine absorption value 1000-1100 mg / g, control the mass ratio of Ketjen black and polyvinylidene fluoride to 8:3, ultrasonic treatment for 30 minutes, to obtain a slurry;
[0103] (3) The dispersed slurry is evenly coated on both sides of the potassium perfluorosulfonic acid cation exchange membrane, with a coating amount of 25 μL / cm 2 , dried at 80 °C for 10 h to obtain a composite membrane, such as Figure 1 As shown in the middle left figure, the prepared composite membrane is a three-layer structure membrane of carbon-containing coating / (transition layer) base membrane (transition layer) / carbon-containing coating.
[0104] Example 2
[0105] A method for preparing a composite diaphragm, wherein each step and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), the mass ratio of Ketjen black to polyvinylidene fluoride is 4:1.
[0106] Example 3
[0107] A method for preparing a composite diaphragm comprises the following steps:
[0108] (1) placing the cut perfluorosulfonic acid cation exchange resin membrane in a 5wt% H2O2 aqueous solution, keeping it at 80°C for 1h, taking out the membrane and placing it in a 5wt% H2SO4 aqueous solution, keeping it at 80°C for 1h; then placing the membrane in a 1mol / L KOH aqueous solution, keeping it at 60°C for 3h, and finally soaking the membrane in deionized water for standby use, to obtain a potassium-type perfluorosulfonic acid cation exchange membrane;
[0109] (2) Polyvinylidene fluoride (PVDF) was dissolved in N-methylpyrrolidone (NMP) and isopropyl alcohol (IPA) in a mass ratio of 2:1 to obtain a transparent polymer solution with a mass fraction of 0.5 wt%. Ketjen black (KB) was weighed and added to the transparent polymer solution. The specific surface area of KB was 1270 m 2 / g, iodine absorption value 1000-1100mg / g, control the mass ratio of Ketjen black and polyvinylidene fluoride to be 4:1, ultrasonic treatment for 60min, to obtain slurry;
[0110] (3) The dispersed slurry is evenly coated on either side of the potassium perfluorosulfonic acid cation exchange membrane, with a coating amount of 50 μL / cm 2 , and dried at 80 °C for 6 h to obtain a composite membrane. Figure 1 As shown in the middle right figure, the prepared composite membrane is a double-layer structure diaphragm containing a carbon coating / (transition layer) base membrane.
[0111] Example 4
[0112] A method for preparing a composite diaphragm, wherein each step of the method and the reagents, equipment and process parameters used in each step are the same as those in Example 3, except that in step (2), Ketjen black (KB) is replaced by activated carbon (AC) in equal amounts, and the specific surface area of the activated carbon is 1100 m 2 / g, iodine absorption value 1000-1100mg / g.
[0113] Example 5
[0114] A method for preparing a composite diaphragm, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 3, except that in step (2), Ketjen black (KB) is replaced by titanium dioxide (TiO2) in equal amounts, and the specific surface area of titanium dioxide is 51.85 m 2 / g, particle size is 60nm.
[0115] Example 6
[0116] A method for preparing a composite diaphragm, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 2, except that in step (2), the mass ratio of Ketjen black to polyvinylidene fluoride is 8:1.
[0117] Comparative Example 1
[0118] A diaphragm for a flow battery comprises the following steps:
[0119] (1) The cut perfluorosulfonic acid cation exchange membrane is placed in a 5wt% H2O2 aqueous solution and kept at 80°C for 1 hour. After the membrane is taken out, it is placed in a 5wt% H2SO4 aqueous solution and kept at 80°C for 1 hour. Then, the membrane is placed in a 1mol / L KOH aqueous solution and kept at 60°C for 3 hours. Finally, the membrane is immersed in deionized water for standby use to obtain a potassium-type perfluorosulfonic acid cation exchange membrane.
[0120] Comparative Example 2
[0121] A method for preparing a composite diaphragm, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 3, except that in step (2), the mass ratio of Ketjen black to polyvinylidene fluoride is 8:16.
[0122] Constant current charge and discharge performance test:
[0123] 1) Sulfur-iodine flow battery: The diaphragms prepared in the above-mentioned Examples 1-2 or Comparative Example 1 were used to assemble the single cells of the sulfur-iodine flow battery, respectively. The battery used a 4 mol / L KI aqueous solution as the positive electrode electrolyte, the negative electrode electrolyte was an aqueous solution containing 1 mol / L KOH, the negative electrode electrolyte contained 3 mol / L K2S2 as the negative electrode active material, and the diaphragm was the diaphragm prepared in Examples 1-2 or Comparative Example 1. The constant current charge and discharge performance test of the above-assembled sulfur-iodine flow battery was carried out. The battery was in a static state, and the positive and negative electrolytes did not flow; the cut-off voltage of the charging process was 1.5V, the cut-off voltage of the discharging process was 0.2V, and the current density was 10mA / cm 2 , the test results are shown in Table 2 below.
[0124] Table 2 - Constant current charge and discharge performance test results of sulfur-iodine flow batteries assembled with membranes of the embodiments and comparative examples
[0125]
[0126] like Figure 2 As shown, the discharge capacity of the sulfur-iodine flow battery assembled with the diaphragm in Example 1 during the cycle process. It can be found that the battery can achieve 100 stable charge and discharge cycles, and the discharge capacity remains at 67Ah / L after 100 cycles. posolyte above; such as Figure 3 As shown, the coulombic efficiency of the sulfur-iodine flow battery assembled with the diaphragm of Example 1 during the cycle process can be found that the coulombic efficiency is still maintained above 99% after 100 cycles, and the average coulombic efficiency is 99.78%.
[0127] like Figure 4 As shown, it is a scanning electron microscope image of the cross section of the composite diaphragm prepared in Example 2. The coating is uniform and dense, without obvious cracks, and the coating thickness is 6-13 μm; Figure 5 As shown, the discharge capacity of the sulfur-iodine flow battery assembled with the diaphragm in Example 2 during the cycle process. It can be found that the battery can achieve 400 cycles of stable charge and discharge cycles, and the discharge capacity remains at 70Ah / L after 400 cycles. posolyte above; such as Figure 6 As shown, the coulombic efficiency of the sulfur-iodine liquid flow battery assembled with the diaphragm of Example 2 during the cycle process can be found that the coulombic efficiency is still maintained above 99% after 400 cycles, and the average coulombic efficiency is 99.78%.
[0128] like Figure 7 As shown in the figure, the discharge capacity of the sulfur-iodine flow battery assembled with the diaphragm in comparative example 1 during the cycle process. It can be found that the discharge capacity begins to decrease after 15 cycles. After 20 charge and discharge cycles, the battery discharge capacity increases from 67.5Ah / L to posolyte Rapidly dropped to 55.45Ah / L posolyte ;like Figure 8 As shown, it is the coulombic efficiency of the sulfur-iodine liquid flow battery assembled with the diaphragm of comparative example 1 during the cycle process. It can be seen that the coulombic efficiency in the first 20 charge and discharge cycles is between 94% and 96%, and the average coulombic efficiency in the first 20 charge and discharge cycles is only 95.15%.
[0129] It is thus shown that the diaphragm of Example 1-2 of the present application uses a slurry made of koheiqin, polyvinylidene fluoride and N-methylpyrrolidone to modify the double-sided surface of the perfluorosulfonic acid cation exchange resin, and the base film interacts with the solvent in the modified layer slurry, so that the base film swells, so that the polyvinylidene fluoride molecules are integrated into the surface of the base film for bonding, and the solvent evaporates during the drying process, and the surface structure of the composite diaphragm is reconstructed, which is manifested as a decrease in the average pore size of the surface of the composite diaphragm after drying, effectively blocking the active material ions; at the same time, the koheiqin in the modified layer has a high specific surface area, which can effectively adsorb the charged active material ions in the electrolyte, and form a charged protective barrier on the membrane surface, thereby hindering the shuttling of the active material. Compared with the untreated base film of Comparative Example 1, the coulombic efficiency of the composite diaphragm assembled sulfur-iodine flow battery of Example 1-2 is higher, indicating that the composite diaphragm has a high ion selective permeability, which can effectively inhibit the shuttling of active materials while conducting carriers, hinder the cross-mixing of positive and negative active materials, avoid the shuttling and degradation of active materials, and achieve excellent cycle stability.
[0130] Among them, the diaphragm prepared in Example 2 contains more Ketjen black than that in Example 1, which can increase the density of Ketjen black in the diaphragm coating, increase the number of charged active substance ions adsorbed on the diaphragm surface, and improve the diaphragm's barrier ability to active substances. Since the key reason for the capacity decay of sulfur-iodine liquid flow batteries is due to the shuttling and degradation of active substances, the diaphragm prepared in Example 2 improves the ability to inhibit the shuttling of active substances, so that the discharge specific capacity of the assembled sulfur-iodine liquid flow battery is significantly improved.
[0131] 2) Sulfur-iron flow battery: The diaphragms prepared in the above-mentioned Examples 3-5 and Comparative Examples 1-2 are used to assemble single cells of the sulfur-iron flow battery. The battery uses an aqueous solution containing 0.5 mol / L K4Fe(CN)6 and 0.5 mol / L Na4Fe(CN)6 as the positive electrode electrolyte, and the negative electrode electrolyte is an aqueous solution containing 1 mol / L KOH. The negative electrode electrolyte contains 1 mol / L K2S4 as the negative electrode active material. The diaphragm is the diaphragm prepared in Examples 3-5 or Comparative Example 1. The constant current charge and discharge performance test of the above-assembled sulfur-iron flow battery was carried out, and the flow rate of the positive and negative electrolytes was 50 mL / min; the cut-off voltage of the charging process was 1.4 V, the cut-off voltage of the discharging process was 0.2 V, and the current density was 20 mA / cm 2 , the test results are shown in Table 3 below.
[0132] Table 3 - Constant current charge and discharge performance test results of the diaphragm-assembled sulfur-iron flow battery of the embodiment and the comparative example
[0133]
[0134] like Fig. 9As shown in FIG. 1 , a scanning electron microscope image of a cross section of a composite membrane prepared in Example 3 is shown. It can be found that the thickness of the coating in the composite membrane is about 13 μm. Fig.10 As shown in the figure, the discharge capacity of the diaphragm-assembled sulfur-iron flow battery in Example 3 during the cycle process. It can be found that the battery can achieve nearly 900 stable charge and discharge cycles, and the discharge capacity is maintained at 25Ah / L posolyte Left and right, such as Fig.11 As shown, this is the coulombic efficiency of the membrane-assembled sulfide-iron flow battery in Example 3 during the cycle process. It can be found that the average coulombic efficiency of the battery in nearly 900 charge and discharge cycles is 99.9%.
[0135] like Fig.12 As shown in the figure, the discharge capacity of the diaphragm-assembled sulfur-iron flow battery in Example 4 during the cycle process. It can be found that the battery can achieve 140 stable charge and discharge cycles, and the discharge capacity remains at 26Ah / L after 140 cycles. posolyte above; such as Fig.13 As shown, this is the coulombic efficiency of the membrane-assembled sulfide-iron flow battery of Example 4 during the cycle process. It can be found that the average coulombic efficiency of the battery after 140 cycles is 99.86%.
[0136] like Fig.14 As shown in the figure, the discharge capacity of the diaphragm-assembled sulfur-iron flow battery in Example 5 during the cycle process. It can be found that the battery can achieve 140 stable charge and discharge cycles, and the discharge capacity remains at 26Ah / L after 140 cycles. posolyte above; such as Fig.15 As shown, this is the coulombic efficiency of the membrane-assembled sulfur-iron liquid flow battery of Example 5 during the cycle process. It can be found that the average coulombic efficiency of the battery after 140 cycles is 99.79%.
[0137] like Fig.16 As shown, the discharge capacity of the diaphragm-assembled sulfur-iron flow battery in comparative example 1 during the cycle process, it can be found that the battery begins to experience capacity decay after the 60th charge and discharge cycle, and the discharge capacity of the first 60 cycles remains at 25Ah / L posolyte The discharge capacity drops to zero after the 72nd cycle. Fig.17 As shown, this is the coulombic efficiency of the membrane-assembled sulfide-iron flow battery of comparative example 1 during the cycle process. It can be found that the coulombic efficiency of the battery during the cycle process fluctuates greatly, and the average coulombic efficiency of the first 70 charge and discharge cycles is only 97.81%.
[0138] like Fig.18 As shown, the first cycle discharge capacity of the diaphragm-assembled iron-sulfur flow battery of Comparative Example 2 is 4Ah / L posolyte , much smaller than the theoretical value (26.8Ah / L posolyte), this is because the proportion of binder in the separator of Comparative Example 2 is too high, the separator resistance is large, and it exhibits a high overpotential, resulting in low battery capacity utilization.
[0139] This shows that the slurry made of filler, polyvinylidene fluoride and N-methylpyrrolidone is used to modify the single or double-sided surface of the perfluorosulfonic acid cation exchange resin. The filler can be Ketjen black, activated carbon or titanium dioxide. The prepared diaphragm can achieve high ion selective permeability when used to assemble sulfur iron liquid flow batteries. The double-layer structure or three-layer structure diaphragm can effectively inhibit the shuttling of active substances and hinder the cross-mixing of positive and negative active substances. Compared with Comparative Example 1, the sulfur iron liquid flow battery assembled with the diaphragm of Examples 3-5 has higher discharge specific capacity, coulomb efficiency, good cycle stability, and extended battery life.
[0140] Due to the strong oxidizing property of iodine, the active material of the positive electrode, the sulfur-iodine flow battery has higher requirements for the chemical stability of the diaphragm compared with other sulfur-based flow batteries such as sulfur-iron flow batteries. At the same time, sulfur and iodine can easily pass through the diaphragm and cause side reactions to the electrodes, resulting in irreversible capacity decay and electrode passivation. Therefore, sulfur-iodine flow batteries have extremely high requirements for the performance of the diaphragm, especially ion permeability and chemical stability.
[0141] 3) Tin-iodine flow battery: The diaphragms prepared in Example 6 or Comparative Example 1 were used to assemble single cells of the tin-iodine flow battery. The battery used a 3 mol / L KI aqueous solution as the positive electrode electrolyte, a 1 mol / L KOH aqueous solution as the negative electrode electrolyte, and a 2 mol / L K2Sn(OH)6 negative electrode electrolyte as the negative electrode active material. The diaphragm was the diaphragm prepared in Example 6 or Comparative Example 1. The above-assembled tin-iodine flow battery was subjected to a constant current charge and discharge performance test. The battery was in a static state, and the positive and negative electrode electrolytes did not flow. The charging process was based on the positive electrode capacity (I - / I3 - )(53.6Ah / L posolyte ) is the cut-off condition, the discharge process cut-off voltage is 0.6V, and the current density is 1.25mA / cm 2 .
[0142] like Fig.19 As shown in the figure, the voltage curve of the tin-iodine liquid flow battery assembled with the diaphragm in Example 6 during the first cycle process, it can be found that the battery can achieve 45Ah / L in the first cycle posolyte The discharge capacity.
[0143] like Fig. 20 As shown, it is the voltage curve of the tin-iodine liquid flow battery assembled with the diaphragm in comparative example 1 during the first cycle. It can be found that the discharge specific capacity of the battery in the first cycle is zero.
[0144] This shows that the surface of the perfluorosulfonic acid cation exchange resin is modified by using a slurry made of koheiqin, polyvinylidene fluoride and N-methylpyrrolidone. The prepared diaphragm can be used to assemble a tin-iodine flow battery to achieve high ion selective permeability and effectively inhibit the shuttling of active substances. When the tin-iodine flow battery is assembled with the unmodified diaphragm on the surface of Comparative Example 1, the iodide ions diffuse from the positive electrode to the negative electrode and react chemically with the tin at the negative electrode, causing irreversible loss of active substances, which manifests as the battery being unable to discharge. Compared with Comparative Example 1, the tin-iodine flow battery assembled with the surface-modified diaphragm in Example 6 has a higher discharge specific capacity and cycle stability.
[0145] 4) Riboflavin sodium phosphate-iron flow battery: The diaphragms prepared in the above-mentioned Examples 2, 4-5 or Comparative Example 1 are used to assemble the single cells of the riboflavin sodium phosphate-iron flow battery, respectively. The battery uses an aqueous solution containing 0.1 mol / L K4Fe(CN)6 as the positive electrode electrolyte, and the negative electrode electrolyte is a 1 mol / L KOH aqueous solution. The negative electrode electrolyte contains 0.1 mol / L riboflavin sodium phosphate (FMN-Na) as the negative electrode active material, and the diaphragm is the diaphragm prepared in Examples 2, 4-5 or Comparative Example 1. The constant current charge and discharge performance test of the above-assembled riboflavin sodium phosphate-iron flow battery is carried out. The flow rate of the positive and negative electrolytes is 50 mL / min, the cut-off voltage of the charging process is 1.4 V, the cut-off voltage of the discharging process is 0.2 V, and the current density is 40 mA / cm 2 , the test results are shown in Table 4 below.
[0146] Table 4 - Constant current charge and discharge performance test results of riboflavin sodium phosphate-iron flow battery assembled with diaphragm of embodiment and comparative example
[0147]
[0148]
[0149] like Fig.21 The discharge specific capacity of the riboflavin sodium phosphate-iron liquid flow battery assembled with the diaphragm of Example 2 during the cycle process is as follows: Fig.23 The discharge specific capacity of the riboflavin sodium phosphate-iron liquid flow battery assembled with the diaphragm of Example 4 during the cycle process is as follows: Fig.25 The discharge specific capacity of the riboflavin sodium phosphate-iron liquid flow battery assembled with the diaphragm of Example 5 during the cycle process is as follows: Fig. 27 The discharge specific capacity of the riboflavin sodium phosphate-iron liquid flow battery assembled with the diaphragm of Comparative Example 1 during the cycle process can be found that the diaphragm assembled batteries of Examples 2, 4-5 and Comparative Example 1 can achieve at least 100 stable charge and discharge cycles, and the discharge specific capacity at the time of 100 cycles is still maintained at 2.8Ah / L posolyte above.
[0150] like Fig. 22The coulombic efficiency of the riboflavin sodium phosphate-iron flow battery assembled with the membrane of Example 2 during the cycle is as follows: Fig.24 The coulombic efficiency of the riboflavin sodium phosphate-iron flow battery assembled with the membrane of Example 4 during the cycle is as follows: Fig.26 The coulombic efficiency of the riboflavin sodium phosphate-iron flow battery assembled with the membrane of Example 5 during the cycle is as follows: Fig.28 The coulombic efficiency of the riboflavin sodium phosphate-iron liquid flow battery assembled with the diaphragm of comparative example 1 during the cycle process is shown. The coulombic efficiency of the diaphragm-assembled batteries of embodiments 2, 4-5 and comparative example 1 can all be maintained above 99% after 100 cycles.
[0151] This shows that the surface of the perfluorosulfonic acid cation exchange resin is modified by a slurry made of filler, polyvinylidene fluoride and N-methylpyrrolidone, and the filler is Ketjen black, activated carbon or titanium dioxide. The discharge specific capacity and coulomb efficiency of the riboflavin sodium phosphate-iron flow battery assembled with the diaphragm of Examples 2, 4-5 and Comparative Example 1 are not much different. It is speculated that the shuttling of active substances in the riboflavin sodium phosphate-iron flow battery is not the key reason for its capacity attenuation, so the use of the surface modified composite diaphragm does not significantly improve the coulomb efficiency of the battery.
[0152] 5) H-type electrolytic cell: An H-type electrolytic cell was assembled using the diaphragm of Example 2 or Comparative Example 1. The right side of the electrolytic cell contained an aqueous solution of 1 mol / L K2S4, which was a dark brown solution. The left side contained an aqueous solution of potassium chloride of the same concentration, which was a transparent solution. The solutions on the left and right sides of the electrolytic cell were separated by a diaphragm, and the volumes of the solutions on both sides were the same. After the experimental device was placed at room temperature (25°C) for 48 hours, the colors of the aqueous solutions on the left and right sides of the electrolytic cell were observed.
[0153] like Fig.29 As shown, the H-type electrolytic cell assembled with the diaphragm of Example 2, the solution on the left side remains transparent, indicating that polysulfides cannot shuttle and are blocked by the diaphragm, indicating that the diaphragm of Example 2 has a good inhibitory effect on the shuttling of polysulfides.
[0154] like Fig.30 As shown, the H-type electrolytic cell assembled with the diaphragm of Comparative Example 1 has a solution on the left side that changes from transparent color to increasingly darker color, indicating that the shuttling of polysulfides is serious, indicating that the diaphragm of Comparative Example 1 has a poor inhibitory effect on the shuttling of polysulfides.
[0155] The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the scope of protection of the present application. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of protection of the present application.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base film and a modified coating located on one side or two opposite sides of the base film, the base film comprises an intermediate layer and a transition layer formed in one piece, the base film is made of a polymer resin, the transition layer is located between the intermediate layer and the modified coating, and the transition layer is formed by the components of the modified coating penetrating into the base film; The components of the modified coating include fillers and binders, the mass ratio of the fillers to the binders is 8:(0.5-5), and the fillers are at least one of carbon materials, mesoporous materials, and metal oxides.
2. A composite diaphragm according to claim 1, characterized in that: The carbon material is at least one of Ketjen black, acetylene black, Super P, activated carbon, carbon nanotubes and graphene, and the mesoporous material is at least one of titanium dioxide, silicon dioxide, aluminosilicate and aluminum oxide.
3. A composite diaphragm according to claim 1, characterized in that: The specific surface area of the filler is 10-3000m 2 / g.
4. A composite diaphragm according to claim 1, characterized in that: The particle size of the mesoporous material is 30-100 nm, and the specific surface area is 20-300 m 2 / g.
5. A composite diaphragm according to claim 1, characterized in that: The filler is a carbon material.
6. A composite diaphragm according to claim 1, characterized in that: The specific surface area of the carbon material is 500-1500m 2 / g.
7. A composite diaphragm according to claim 1, characterized in that: The carbon material has an iodine adsorption value of 500 mg / g or more.
8. A composite diaphragm according to claim 1, characterized in that: The filler is Ketjen black, and the specific surface area of the Ketjen black is 1200-1500m 2 / g, and the iodine adsorption value is 1000-1100mg / g.
9. A composite diaphragm according to claim 1, characterized in that: The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, perfluoroethylene propylene copolymer and modified materials of the above substances.
10. A composite diaphragm according to claim 1, characterized in that: The polymer resin is at least one of perfluorosulfonic acid resin, polysulfone resin, polyimide resin, polyvinylidene fluoride resin, polyaryletherketone resin, polyethersulfone resin, polybenzimidazole resin, polyacrylamide resin, sulfonated polysulfone resin, sulfonated polyimide resin, sulfonated polyvinylidene fluoride resin, sulfonated polyaryletherketone resin, sulfonated polyethersulfone resin, sulfonated polybenzimidazole resin and sulfonated polyacrylamide resin.
11. A composite diaphragm according to claim 1, characterized in that: The slurry of the modified coating includes fillers and an organic solvent containing a binder. The mass ratio of the filler to the binder is 8:(0.5-5). The mass fraction of the binder in the organic solvent containing the binder is 0.01wt%-5wt%.
12. A composite diaphragm according to claim 11, characterized in that: The organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, n-propanol, isopropanol, ethanol, isobutanol, tetrahydrofuran, ethylene glycol, methanol, dimethyl sulfoxide and acetonitrile.
13. A method for preparing a composite diaphragm according to any one of claims 1 to 12, characterized in that: The following steps are involved: (1) dissolving the binder in an organic solvent, then adding a filler and dispersing the mixture evenly to obtain a slurry; (2) The slurry is evenly coated on one side or two opposite sides of the base film and dried to obtain a composite diaphragm.
14. The method for preparing a composite diaphragm according to claim 13, characterized in that: In step (2), the base membrane is a potassium-type perfluorosulfonic acid cation exchange resin membrane obtained by activation treatment of a perfluorosulfonic acid cation exchange resin membrane.
15. The method for preparing a composite diaphragm according to claim 13, characterized in that: In step (1), the ultrasonic dispersion time is 10-60 min; in step (2), the coating amount is 5-1000 μL / cm 2 ; In step (2), the drying temperature is 60-120°C and the drying time is 5-15h.
16. Use of the composite membrane according to any one of claims 1 to 15 in preparing a flow battery, characterized in that: The liquid flow battery is a sulfur-based liquid flow battery, an iodine-based liquid flow battery, a sulfur-iodine liquid flow battery or a bromine-based liquid flow battery.